Corporate social responsibility in global and local companies of Southeast Europe - Čibukčić, Fuad (Industrija, 2017)
The aim of this work is the analysis of theoretical assumptions and empirical research to find the answer to the question on how the activities in the field of corporate social responsibility in the region of Southeast Europe are present in the business of global and local companies market. Whether and to what extent to implement socially responsible behavior of companies with a different ownership structure, the revenue volume, market share, market activities and markets where it operates, and if the objectives of the companies are in line with the goals of social communities. they offer other than legal, and more benefits for their employees and provide them extra protection, whether, and to what extent, the state helps in carrying out socially useful activities and the compliance of the company’s positive legal norms and international standards? The result of the research offered the conclusion that social responsibility activities in companies market of SE Europe are present in an increasing scope, a CSR program contributes to the awareness of the importance and necessity of such activities in the construction of a positive corporate image and relations of the companies with communities and stakeholders in the region.